Thursday
March 23, 2017

Post a New Question

Posted by on Monday, March 5, 2012 at 4:24pm.

SIMPLIFY

1.(3+√2)/√2

2. 4/(1+√3)

3.(3+√5)(1-2√5)

4.(3+√8)/((2√3)-4)

  • Math - , Monday, March 5, 2012 at 4:28pm

    Square root.

  • Math - , Monday, March 5, 2012 at 4:35pm

    (3+√2)/√2 = (3√2 + 2)/2

    4/(1+√3) * (√3-1)/(√3-1) = 4(√3-1)/(3-1) = 2(√3-1)

    (3+√5)(1-2√5) = 3 -5√5 - 10 = -7-5√5

    (3+√8)/((2√3)-4) * (2√3 + 4)/(2√3 + 4)
    = (3+√8)(2√3 + 4)/(12-16)
    = (6√3 + 2√24 - 12 - 4√8)/-4
    = (12 + 8√2 - 6√3 - 4√6)/4

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question